Depressive symptoms and traumatic dental injuries among adolescents. Issue 2 (20th November 2019) - Randhawa, Shanza S.; Marcenes, Wagner; Stansfeld, Stephen A.; Bernabé, Eduardo
Abstract: Background/Aim: A previous cross‐sectional study found that young adults with depression were more likely to have traumatic dental injuries (TDIs). The aim of this study was to determine the relationship between depressive symptoms during early and middle adolescence, and TDIs at age 15‐16 years. Method: This study used longitudinal data from phases 1 and 3 of the Research with East London Adolescents Community Health Survey (RELACHS), a school‐based survey following a representative, multi‐ethnic sample of adolescents attending public schools in East London (England). Information on depressive symptoms was collected using the Short Moods and Feelings Questionnaire (SMFQ) during early (age 11‐12 years) and middle adolescence (age 15‐16 years). TDIs were identified during clinical examinations in phase 3 when pupils were 15‐16 years old. Logistic regression was used to test the association between depressive symptoms at different stages of adolescence and TDIs adjusting for confounders (age, gender, ethnicity, parental employment and overjet). Results: Depressive symptoms were reported by 24% and 32% of adolescents in early and middle adolescence, respectively. Evidence of TDIs was found in 18% of adolescents at age 15‐16 years. Adolescents with depressive symptoms, either in early or middle adolescence, had greater odds of experiencing TDIs. However, these estimates were not statistically significant. In regression models adjusted for confounders, the odds of having TDIs were 1.23 (95% CI: 0.77‐1.96) and 1.23 (95% CI: 0.76‐1.95) among pupils with depressive symptoms in early and middle adolescence, respectively. Conclusion: There was no association between depressive symptoms and TDIs in early and middle adolescents.